Gender stereotypes between men and women in society and how they shape us - Dimaano, Marie Angelique I. (2013)
Men and women are created different; they have some differences in brain structure, body structure, hormones, and in other physiological aspects. These differences affect how men and women behave and may provide explanations for some beliefs that society has now regarding the sexes, i.e. why women are more emotional, why men are physically stronger, et cetera. The biological differences that men and women have also explain certain gender roles in a nonsexist way, why there are things better done by men and things that are better done by women like child-rearing and tasks which require great physical strength. However, these gender roles, when exaggerated, lead to beliefs that are not entirely true, forming standards that tell how men and women should think, act and look. Therefore leading people to generalize gender groups. Gender has been a big factor in shaping one's personality. Society has imposed certain pressures on people based on their gender, like how men should not show any weakness and how women should make themselves beautiful. These pressures are not entirely negative but with these pressures, there should be awareness and the freedom to decide on who a person wants to be.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Sex differences